2014
DOI: 10.5817/ai2014-1-51
|View full text |Cite
|
Sign up to set email alerts
|

Zkušenost s halucinogenní rostlinou ayahuasca v kontextu šamanského rituálu

Abstract: EXPERIENCE WITH HALLUCINOGENIC PLANT AYAHUASCA IN THE CONTEXT OF SHAMANIC RITUAL ABSTRAKT Výzkum je zaměřen na osoby, které se vydaly do amazonských pralesů užívat přírodní halucinogen ayahuasku v kontextu "šamanského" rituálu. Tento jev popisovaný antropology od 70. let. 20. stol. jako tzv. "šamanský turismus" je stále aktuálnější především mezi obyvateli zemí Evropy a USA. Našim cílem bylo zmapovat, jakým způsobem ayahuaskový šamanský turismus probíhá-motivaci osob, které tento druh zkušenosti vyhledávají, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 27 publications
0
1
0
3
Order By: Relevance
“…Ayahuasca became popular outside the Amazon in the 1990s, and since has seen a rise in use around the world, as well as in "ayahuasca tourism," in which individuals travel to the Amazon in order to participate in rituals [ 34 , 37 ]. Though ayahuasca tourism is criticised as being a radicalised form of recreational drug use, research suggests that users undergoing these voyages do so seeking spiritual growth or to help with psychological conditions [ 38 , 39 ].Though legally questionable in many countries outside of Amazonia, its status as a spiritual sacrament for some recognised religious groups has led to increased acceptance [ 40 – 46 ]. Previous research in France has suggested that usage of ayahuasca is low, with only 4 out of 30 individuals in a study having made use of it [ 8 ].…”
Section: Resultsmentioning
confidence: 99%
“…Ayahuasca became popular outside the Amazon in the 1990s, and since has seen a rise in use around the world, as well as in "ayahuasca tourism," in which individuals travel to the Amazon in order to participate in rituals [ 34 , 37 ]. Though ayahuasca tourism is criticised as being a radicalised form of recreational drug use, research suggests that users undergoing these voyages do so seeking spiritual growth or to help with psychological conditions [ 38 , 39 ].Though legally questionable in many countries outside of Amazonia, its status as a spiritual sacrament for some recognised religious groups has led to increased acceptance [ 40 – 46 ]. Previous research in France has suggested that usage of ayahuasca is low, with only 4 out of 30 individuals in a study having made use of it [ 8 ].…”
Section: Resultsmentioning
confidence: 99%
“…Dále v České republice vyšly originální práce věnované šamanskému turismu (Kavenská, Simonová, 2014) a motivaci českých účastníků ayahuascových obřadů pořádaných v Evropě (Kavenská, Vosáhlová, 2013). Před časem jsme publikovali první odbornou studii o glokalizaci ayahuascy a možnostech jejího terapeutického využití v místních podmínkách (Horák et al, 2015).…”
Section: Lokalizace Ayahuascy V čEské Republiceunclassified
“…K lidem, kteří se na ayahuasková sezení vydávají, patří nejen domorodci, ale také zahraniční pacienti a experimentátoři (Kavenská a Simonová, 2014). V souvislosti s tím lze hovořit o tzv.…”
Section: Tradiční Amazonská Medicínaunclassified